Improving Learning Outcomes Through Direct Learning Models Using Concrete Image Media - Dian Evi Styaningsih; Yuyun Bahtiar; Iin Baroroh Ma’arif; Nur Khasibah (SCHOOLAR: Social and Literature Study in Education, 2025)
The acquisition of mathematical knowledge in Public Primary School 2 Sumber Mukti encountered several obstacles, namely the lack of student motivation in the following lessons. The lack of enthusiasm and apathy shown by students during the learning process had a negative impact on their academic achievement. To overcome this problem, a direct learning strategy was used by utilizing concrete visual media. This study aims to improve student learning outcomes and describe learning activities related to the concept of addition and subtraction. This study is a classroom action research (CAR) conducted in class II of Public Primary School 2 Sumber Mukti, with 9 students. The research methodology was carried out in two cycles, with each cycle consisting of four stages: planning, implementation, observation, and reflection. Data collected on student learning outcomes through written evaluations were then examined qualitatively in a descriptive manner, emphasizing the extent of student achievement. The study showed that the use of concrete visual media improved student learning outcomes. In Cycle I, out of 9 students, 4 students achieved learning completion, while 5 students did not, so the percentage of completion was 40%, which was still below the minimum threshold for classical completion. In Cycle II, the number of students who completed the program increased to 7 students, while 2 students still had not completed it, so the completion percentage was 70%, thus meeting the minimum threshold for classical completion.